2011
DOI: 10.1039/c0ob00455c
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increase of quench efficiency in “spacerless” dimaleimide fluorogens

Abstract: In this post-genomic era, new techniques are needed to cope with the task of assigning functional roles to the huge number of identified putative gene products. We have developed a minimalist labelling strategy based on the use of synthetic fluorogenic probe reagents that fluoresce only after their reaction with a target peptide sequence. The probe reagents have fluorescent cores and bear two maleimide groups, such that their latent fluorescence is quenched by a photoinduced electron transfer (PET) to the pend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…We first investigated the spectroscopic properties of 17 in detail. It is known that maleimides often quench the luminescence of chromophores,23, 31, 32 and as compound 17 shows almost no fluorescence at all, it is indicated that such quenching is observed here. The fluorescence intensity and lifetime of 17 increase strongly upon reaction of the double bond of the maleimide with a thiol (e.g., cysteine) to form the corresponding thioether 18 .…”
Section: Resultsmentioning
confidence: 69%
“…We first investigated the spectroscopic properties of 17 in detail. It is known that maleimides often quench the luminescence of chromophores,23, 31, 32 and as compound 17 shows almost no fluorescence at all, it is indicated that such quenching is observed here. The fluorescence intensity and lifetime of 17 increase strongly upon reaction of the double bond of the maleimide with a thiol (e.g., cysteine) to form the corresponding thioether 18 .…”
Section: Resultsmentioning
confidence: 69%
“…[16] This carboxylic acid was treated with base and chloromethyl chlorosulfate according to the procedure of Graham et al [17] to obtain the chloromethyl ester 6 . To determine if this coumarin derivative would be cleaved within a cell to release a phosphoantigen, we prepared a derivative of the phosphonate 7 , which we have found does not itself stimulate Vγ9Vδ2 T-cells.…”
mentioning
confidence: 99%
“…The structures of the tris(triazolo)benzene and its derivatives are supported by IR, 1 H, 13 C NMR and, in some cases, 15 N NMR spectroscopic data as well as elemental analysis (or high-resolution mass spectrometry, HRMS). The 13 C NMR spectra of 8 showed only a single peak at 132 ppm in [D 6 ]DMSO (dimethylsulfoxide), which suggests that the hydrogen is shifting from the N1 to the N3 nitrogen atom of the triazole rings of tris(triazolo)benzene.…”
Section: Methodsmentioning
confidence: 99%
“…When the potassium salt of tris(triazolo)benzene was treated with oxone, the trihydroxy derivative (15) was not produced (Scheme 4). When the potassium salt of tris(triazolo)benzene was treated with oxone, the trihydroxy derivative (15) was not produced (Scheme 4).…”
Section: Methodsmentioning
confidence: 99%